2019
DOI: 10.1037/dev0000821
|View full text |Cite
|
Sign up to set email alerts
|

Maternal reminiscing and child autobiographical memory elaboration: A meta-analytic review.

Abstract: Significant research has investigated the relationship between mother–child reminiscing and children’s autobiographical memory development. It has been suggested that mothers who adopt a high elaborative reminiscing style tend to have children who provide greater memory elaboration during joint reminiscing, yet the empirical findings are somewhat mixed. To address this issue, a systematic review and meta-analyses were conducted to investigate the relationship between maternal elaborative reminiscing and child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
36
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 83 publications
6
36
2
Order By: Relevance
“…In particular, maternal reminiscing uniquely predicted a high proportion of variance, even after controlling for other factors. Thus, our findings further support a pan‐cultural association between maternal reminiscing styles and child memory elaboration (Nelson & Fivush, 2004; Schröder et al, 2012; Wang, 2007; Wu & Jobson, 2019). Nonetheless, only child age and language emerged as unique predictors of child memory specificity.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In particular, maternal reminiscing uniquely predicted a high proportion of variance, even after controlling for other factors. Thus, our findings further support a pan‐cultural association between maternal reminiscing styles and child memory elaboration (Nelson & Fivush, 2004; Schröder et al, 2012; Wang, 2007; Wu & Jobson, 2019). Nonetheless, only child age and language emerged as unique predictors of child memory specificity.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous research comparing dyads (of similarly well-educated urban background) from autonomy-oriented and relatednessoriented cultural contexts (e.g., Schr€ oder et al, 2012;Wang, 2007), our findings indicated that Australian mothers were more elaborative than Chinese mothers during reminiscing. Specifically, Australian mothers used significantly more wh-questions and confirmations (i.e., the two critical aspects of an elaborative reminiscing style that have been identified in past research; for a review, see Wu & Jobson, 2019) than Chinese mothers. In addition, Australian mothers were rated as significantly more supportive (in recognizing, validating, and encouraging children's contribution to the conversation) than Chinese mothers in reminiscing.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations